Phase transformations - Soustelle, Michel (Chemical engineering series: chemical thermodynamics set, 2016)
The book offers advanced students, in 7 volumes, successively characterization tools phases, the study of all types of phase, liquid, gas and solid, pure or multi-component, process engineering, chemical and electrochemical equilibria, the properties of surfaces and phases of small sizes. Macroscopic and microscopic models are in turn covered with a constant correlation between the two scales. Particular attention was given to the rigor of mathematical developments. Besides some very specialized books, the vast majority of existing works are intended for beginners and therefore limited in scope. There is no obvious connection between the two categories of books, general books does not go far enough in generalizing concepts to enable easy reading of advanced literature. The proposed project aims to give readers the ability to read highly specialized publications based on a more general presentation of the different fields of chemical thermodynamics. Consistency is ensured between the basic concepts and applications. So we find, in the same work, the tools, their use and comparison, for a more general macroscopic description and a microscopic description of a phase.